Replicação de índices de renda fixa em carteiras : caso do IMA-Geral - Fonseca, Renato Lobato (2017)
In this study, we discuss the index tracking problem in the context of passive investing strategy for mutual funds. A minimization of tracking error model was created using the variance-covariance matrix and expected return estimation based on historical returns in order to track the Brazilian fixed income index called Índice de Mercado Anbima, IMA-G. This is the first study to approach the indexation of IMA-G. The model was tested in a out-of-sample simulation, and the results showed good quality in the indexation with only 60% of the bonds allocated in the index.